Designing a Village Letter Filing System as an Effort to Improve Administrative Efficiency in Suka Muda Village (Case Study in Suka Muda Village) - Ummy Calsum; Apriansyah; Zulhipni Reno Saputra Pandiati; Karnadi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In the use of information technology, including the system of archiving incoming mails, outgoing letters are very important to support organizational development in terms of operational activities. This is because with the existence of an archiving system in an organization, it can speed up a work process and can make it easier to manage letters and make letters more organized and neat. The researcher sees that there are problems in the Sukamuda village letter filing system where at this time, the procedures applied to the management of incoming and outgoing letters in Sukamuda village, starting from receipt, storage, documentation, to letter verification, are all carried out conventionally. This research aims to make it easier to archive incoming and outgoing letters by developing a website-based archiving application . The research method used is the Development (R&D) method, observation data collection techniques and literature studies, the system development model used in this study is the Waterfall Model. Waterfall is one of the Software Development Life Cycles (SDLC) where software development activities start from specification, development, validation, and evolution and then divide it into phases and final testing using the Black Box method. With the implementation of this system, it is hoped that it can overcome problems in the application of letter archiving, especially at the letter stage in villages like to move.